INCIDENT OF DRY EYE IN FK UNDIP STUDENTS USING SMARTPHONES - Adella Setyo Purnomo; Arief Wildan; Fifin Luthfia Rahmi; Arnila Novitasari Saubig (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Smartphone use is increasing over time and often causes Dry Eye Syndrome (DES). Dry Eye Syndrome (DES) is a multifactorial disease of the ocular surface characterized by loss of homeostasis and causes various ocular symptoms. The Schirmer test is a measurement of the tears quantity to diagnose DES. Objective: To determine the effect of smartphone use on the results of Schirmer test measurements. Methods: This was a quasi-experimental research with a pre-test and post-test design. The research subjects consisted of 36 students selected based on inclusion and exclusion criteria using consecutive sampling. The experimental group (n=18) used a smartphone for 2 hours by watching the video (film), while the control group (n=18) did not use the smartphone. Schirmer tests were carried out before and after observation for 5 minutes using Schirmer paper strips. Statistical tests used the Shapiro-Wilk test with a meaning value of p ≥ 0,05, Chi-square test, Paired t-test, Wilcoxon test, and Mann-Whitney test with a meaning value of p < 0,05. Results: There was a significant decrease in the Schirmer test results (p = 0,020) by 1,334 ± 0,8937 mm in the experimental group and a non-significant increase (p = 0,582) in the control group by 0,362 ± 0,4086 mm. There was a significant difference in the decrease of Schirmer test results between the experimental group compared to the control group (p = 0,048). Conclusion: The use of smartphones influences the decrease in Schirmer test measurement results.